An Open Platform for Full Body Interactive Sonification Exergames - Simone Ghisio; Paolo Coletta; Stefano Piana; Paolo Alborno; Gualtiero Volpe; Antonio Camurri; Ludovica Primavera; Carla Ferrari; Carla Guenza; Paolo Moretti; Valeria Bergamaschi; Andrea Ravaschio (EAI Endorsed Transactions on Serious Games, 2015)
This paper addresses the use of a remote interactive platform to support home-based rehabilitation for children with motor and cognitive impairment. The interaction between user and platform is achieved on customizable full-body interactive serious games (exergames). These exergames perform real-time analysis of multimodal signals to quantify movement qualities and postural attitudes. Interactive sonification of movement is then applied for providing a real-time feedback based on “aesthetic resonance” and engagement of the children. The games also provide log file recordings therapists can use to assess the performance of the children and the effectiveness of the games. The platform allows the customization of the games to address the children’s needs. The platform is based on the EyesWeb XMI software, and the games are designed for home usage, based on Kinect for Xbox One and simple sensors including 3-axis accelerometers available in low-cost Android smartphones.